A fast and responsive voltage indicator with enhanced sensitivity for unitary synaptic events. - Hao, Y.A.; Lee, S.; Roth, R.H.; Natale, S.; Gomez, L.; Taxidis, J.; O'Neill, P.S.; Villette, V.; Bradley, J.; Wang, Z.; Jiang, D.; Zhang, G.; et al. (Neuron, 2024)
A remaining challenge for genetically encoded voltage indicators (GEVIs) is the reliable detection of excitatory postsynaptic potentials (EPSPs). Here, we developed ASAP5 as a GEVI with enhanced activation kinetics and responsivity near resting membrane potentials for improved detection of both spiking and subthreshold activity. ASAP5 reported action potentials (APs) in vivo with higher signal-to-noise ratios than previous GEVIs and successfully detected graded and subthreshold responses to sensory stimuli in single two-photon trials. In cultured rat or human neurons, somatic ASAP5 reported synaptic events propagating centripetally and could detect ?1-mV EPSPs. By imaging spontaneous EPSPs throughout dendrites, we found that EPSP amplitudes decay exponentially during propagation and that amplitude at the initiation site generally increases with distance from the soma. These results extend the applications of voltage imaging to the quantal response domain, including in human neurons, opening up the possibility of high-throughput, high-content characterization of neuronal dysfunction in disease.